2017
DOI: 10.1002/aic.15697
|View full text |Cite
|
Sign up to set email alerts
|

Role of free surface on gas‐induced liquid mixing in a shallow vessel

Abstract: The present work is carried out to understand the effect of free surface on liquid velocity distribution, dynamics and liquid phase mixing in a shallow basic oxygen furnace (BOF). Three‐dimensional/transient Euler–Lagrange (EL) without/with volume‐of‐fluid (VOF) simulations of dispersed gas–liquid flow in a scaled‐down model of the BOF were performed. For lower H/D ratios, EL simulations performed with no‐slip and free‐slip boundary conditions led to oscillatory plume behavior and higher liquid velocity region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Gupta et al (2016) used a coupled VOF and pseudotransient method to solve free-surface flow problems, and the numerical solution compared well with analytical or experimental data. Quiyoom et al (2017) simulated the process of gas-induced liquid mixing in a shallow vessel and found that the mixing time predicted by EL + VOF was in good agreement with the measurements.…”
Section: Introductionmentioning
confidence: 56%
“…Gupta et al (2016) used a coupled VOF and pseudotransient method to solve free-surface flow problems, and the numerical solution compared well with analytical or experimental data. Quiyoom et al (2017) simulated the process of gas-induced liquid mixing in a shallow vessel and found that the mixing time predicted by EL + VOF was in good agreement with the measurements.…”
Section: Introductionmentioning
confidence: 56%
“…Pang et al (2020) presented a T-form microfluidic device with a neck at the junction and evaluate droplet volume under several flow rates. Quiyoom et al (2017) deciphered the free surface effect on liquidphase mixing in shallow vessels. Redapangu et al (2021) analyzed the effect of changing density and viscosity of two immiscible liquids in a 3-D inclined microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in most of the studies, single‐point measurements were performed to measure the mixing time in the vessel with the assumption of symmetric mixing. Recently, Quiyoom et al 20 performed mixing time measurements with multiple conductivity probes simultaneously in a 1:6 scaled‐down cold‐flow model of the BOF vessel and showed asymmetric mixing behavior in the vessel, that is, the local mixing time varied considerably from one location to other location. Therefore, to understand the reasons for asymmetric flow and mixing behavior quantitatively, whole‐field measurements (PIV and planar laser‐induced fluorescence [PLIF]) are required.…”
Section: Introductionmentioning
confidence: 99%